Let’s put mental health problems and related issues appropriately in social media: A voice of psychiatric nurses - Fauzan Saputra; Penpaktr Uthis; Sunisa Sukratul (Belitung Raya Foundation, Indonesia, 2023)
Social media is one convenient way to express ourselves. Much information is offered; most is difficult to filter and can be consumed by anyone, anywhere, anytime. However, sometimes it crosses the boundaries of someone else’s life or privacy, especially when discussing sensitive issues, such as mental health problems. There are a lot of discussions about whether bringing the personal experiences of people with mental health problems to the public domain can potentially increase the community’s attitudes toward them or not. Still, one thing is for sure, this kind of content has caught public attention by having more viewers. Unfortunately, it potentially brings other consequences for people with mental health problems, such as stigmatization, discrimination, and sadfishing. Therefore, this paper aims to provide the viewpoints of psychiatric nurses regarding how to address mental health-related issues and appropriately put content about mental health problems on social media.